"Cross‐Dressing" Becomes Fashionable Among Transplant Recipients. Issue 1 (26th September 2016) - Burlingham, W. J.
Abstract : Alloantigen "direct" presentation, once thought to be a transient phase mediated by cells that emigrate from the vascularized graft, re‐emerges as the much more formidable and ongoing "semi‐direct" pathway—driven not by donor cells per se but by their exosomes that "cross‐dress" the surface of host APC with intact allo‐MHC. See Smyth et al's article onpage 60 .